‘Remoteness was a blessing, but also a potential downfall’: traditional/subsistence and store-bought food access in remote Alaska during the COVID-19 pandemic - Ruby L Fried; Micah B Hahn; Patricia Cochran; Laura P Eichelberger (Public Health Nutrition, 2023)
Abstract